Medical care and treatment of children with asthmatic or wheezing health outcomes and urban–rural differences in Bavaria – a cross-sectional study. (13th June 2022) - Kutzora, Susanne; Herrera Reyes, Daniela; Weinberger, Alisa; Huß, Jonas; Nennstiel, Uta; von Mutius, Erika; Herr, Caroline; Heinze, Stefanie
Abstract: Introduction: Asthma is among the most common chronic conditions in children. The aim of this publication is to describe prevalence rates and factors associated with asthmatic or wheezing preschoolers and to evaluate medical care and treatment with regard to urban–rural differences. Methods: Data for this cross-sectional study were collected through a questionnaire, which was distributed to parents within the Health Monitoring Units in Bavaria (HMU), Germany. Data from 4767 children were available (2016/17). Those children were classified into four diagnostic groups: Unremitting Wheeze, International Study of Asthma and Allergies in Children (ISAAC) Asthma, Physician-diagnosed Asthma, and healthy control group. Urban–rural differences were tested by Pearson's chi-squared test or by Fisher's exact test. Independent variables were factors associated with health outcomes, for example, residency or migrant status. To examine associations between independent and outcome variables multivariate logistic regression analysis was performed. Results: Prevalence rates were 6.3% for 'Unremitting Wheeze', 5.2% for 'ISAAC Asthma', and 1.2% for 'Physician-diagnosed Asthma'. Factors associated with health outcomes were the occurrence of asthma in first-degree relatives, male sex, and migrant status. Generally, higher rates of doctor's visits, positive allergy tests, and corticosteroids intake in the diagnostic groups in rural compared to urban areas were observed. Rates of performed allergy tests were 55.6% for 'ISAAC Asthma' and 74.6% for 'Physician-diagnosed Asthma'. Conclusions: Prevalence rates of the diagnostic groups decreased compared to the HMU 2014/15. According to previous studies, factors associated with asthmatic or wheezing health outcomes could be confirmed. Children in rural areas generally received more medical care. Key points: Children's prevalence rates of asthma or wheezing disorders decreased in the past 2 years within Bavaria. This study is consistent with risk factors for asthma from the literature: asthma in the family, male gender, and migrant status. Children in rural areas receive more medical care than children in urban areas. There should me more allergy tests among children with medical diagnosis in Bavaria as low rates indicate gaps in care.